Optically Induced Nonlinear Cubic Crystal System for 3D Quasi‐Phase Matching. Issue 4 (18th January 2022) - Chen, Yesheng; Yang, Chen; Liu, Shan; Wang, Sen; Wang, Ningning; Liu, Yongxing; Sheng, Yan; Zhao, Ruwei; Xu, Tianxiang; Krolikowski, Wieslaw
Abstract : Quasi‐phase matching (QPM) is a technique in nonlinear optics for achieving efficient energy exchange among optical waves at different frequencies, by spatially modulating the quadratic nonlinearity ( χ (2) ) of the medium. To realize the full potential of QPM, 3D spatial modulation of χ (2) is required. This has become experimentally feasible recently thanks to the invention of femtosecond laser‐based nonlinearity engineering in ferroelectric crystals. Herein, the first experimental demonstration of QPM second harmonic generation (SHG) in a nonlinear cubic crystal system is presented, in which χ (2) modulations form simple cubic, body‐centered cubic, face‐centered cubic, and diamond cubic lattices, respectively. The experimental results indicate that these nonlinear cubic structures share the same primary reciprocal lattice vectors (RLVs), but possess different Fourier coefficients (in conventional cells), leading to SHG with similar angular resonances but various intensity distributions in the far field. This work contributes to a comprehensive understanding of nonlinear optical processes in 3D periodic media, and thus sheds light on the development of high‐performance QPM devices. Abstract : Nonlinear cubic photonic crystals refer to three‐dimensional microstructures where the quadratic nonlinearity of the medium is modulated to form a cubic lattice. Herein, the first fabrication of nonlinear cubic photonic crystals using the femtosecond‐laser‐induced ferroelectric domain inversion technique is presented. The quasi‐phase matching properties of such crystals are also studied to inspire novel applications in laser frequency conversions.